2014
DOI: 10.3171/2014.4.spine13627
|View full text |Cite
|
Sign up to set email alerts
|

Paraspinal muscle morphometry in cervical spondylotic myelopathy and its implications in clinicoradiological outcomes following central corpectomy

Abstract: Object The objective of this study was to assess the cross-sectional areas (CSAs) of the superficial, deep flexor (DF), and deep extensor (DE) paraspinal muscles in patients with cervical spondylotic myelopathy (CSM), and to evaluate their correlations with functional status and sagittal spinal alignment changes following central corpectomy with fusion and plating. Methods In this retrospective study of … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
31
0

Year Published

2016
2016
2020
2020

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 36 publications
(34 citation statements)
references
References 32 publications
3
31
0
Order By: Relevance
“…Using the formula for sample size calculation for paired means and incorporating the clinically meaningful difference in CSA values from a previous study on cervical PSMs, 21 a sample size of 25 was determined to be adequate to obtain a power of 0.9 for the study. Data were entered in an Excel spreadsheet (Microsoft, Inc.) and analyzed using SPSS version 20.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Using the formula for sample size calculation for paired means and incorporating the clinically meaningful difference in CSA values from a previous study on cervical PSMs, 21 a sample size of 25 was determined to be adequate to obtain a power of 0.9 for the study. Data were entered in an Excel spreadsheet (Microsoft, Inc.) and analyzed using SPSS version 20.…”
Section: Discussionmentioning
confidence: 99%
“…The crosssectional area (CSA) measurement method was based on the technique standardized in previous studies. 1,21 Digital images of the preoperative cervical spine MRI were retrieved from the hospital radiographic system (Synapse, Fujifilm Health Systems). MR images were acquired on an HDi 1.5-T magnet (GE Signa) using a standard neurovascular coil.…”
Section: Radiographic Evaluationmentioning
confidence: 99%
See 1 more Smart Citation
“…Given the strong correlations established between muscle mass and skeletal CSA, 32 we assumed that the muscle areas biomechanically corresponded to the morphometry of the vertebral body (VB) at any given level. 33 Thus, muscle CSA/VB CSA ratios (rather than absolute muscle CSA values) were used to eliminate biases arising from variations in patient build. The CSA of the VB was measured at the same cuts as those taken for the measurement of the muscle areas.…”
Section: Radiographic Evaluationmentioning
confidence: 99%
“…Nontraumatic neck pain patients have been shown to demonstrate atrophy in most of the deep posterior compartment muscles (Elliott et al, ) whereas in chronic tension‐type headache, selective atrophy has been observed in the rectus capitis posterior major and minor muscles with relative sparing of semispinalis and splenius capitis (Fernandez‐de‐Las‐Penas et al, ). In contrast, patients with cervical spondylotic myelopathy have been shown to have atrophy in both the anterior and posterior, deep and superficial muscles (Thakar et al, ). Cervical nerve root avulsion following brachial plexus traction injuries is accurately identified by increased enhancement of multifidus in particular (Hayashi et al, ).…”
Section: Introductionmentioning
confidence: 99%